2018
DOI: 10.1039/c8cp04244f
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of dynamic, tunnelling and kinetic isotope effects in formate dehydrogenase

Abstract: The protein cannot be considered as a passive spectator of the chemical system; it is part of the chemical reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 108 publications
(187 reference statements)
1
5
0
Order By: Relevance
“…The resulting KIE was found to be 3.89 AE 0.15 when the ground state of BNAH in aqueous solution was used, and this parameter further increased to 4.28 AE 0.18 when the equilibrium between the Michaelis complex and the hydride transfer transition state were used for calculation (see ESI, † for details). These values are similar to those previously obtained for hydride transfer processes catalyzed by NADH-dependent enzymes, 35,36 including L-lactate dehydrogenase (in the range between 3.36 and 2.80) 37 and morphinone reductase (8.4 AE 1.6), 38 but significantly higher than that of the experimental counterpart measured in the present study. Interestingly, regarding the hydride donor-acceptor distance and the relative orientation of the different involved moieties, the nature of the optimized transition state can be considered as equivalent to those located in previous studies (Fig.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The resulting KIE was found to be 3.89 AE 0.15 when the ground state of BNAH in aqueous solution was used, and this parameter further increased to 4.28 AE 0.18 when the equilibrium between the Michaelis complex and the hydride transfer transition state were used for calculation (see ESI, † for details). These values are similar to those previously obtained for hydride transfer processes catalyzed by NADH-dependent enzymes, 35,36 including L-lactate dehydrogenase (in the range between 3.36 and 2.80) 37 and morphinone reductase (8.4 AE 1.6), 38 but significantly higher than that of the experimental counterpart measured in the present study. Interestingly, regarding the hydride donor-acceptor distance and the relative orientation of the different involved moieties, the nature of the optimized transition state can be considered as equivalent to those located in previous studies (Fig.…”
supporting
confidence: 92%
“…3). [35][36][37][38] It therefore suggests that the hydride transfer step in the T-Sav artificial enzyme is at least partially rate-limiting.…”
mentioning
confidence: 99%
“…Computational studies of FDH have identified important interactions in the active site, first, in classical simulations by Bruice 36 and, later, in QM/MM studies by Popov. 35 Freeenergy calculations by Moliner, 37 with the use of the AM1 semiempirical Hamiltonian, found a free-energy barrier equal to 12.1 kcal/mol.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In Tyr196AzAla a VET pathway along NAD + is highly probable, which requires efficient VET between three molecules, from FDH to NAD + and from NAD + to N − 3 . In the previous study on Pseudomonas FDH, motions of various active-site residues were identified as integral part of the reaction coordinate [263]. Because of the high sequential and structural similarity to Cb FDH, these residues can clearly be identified as Val93, 1 Because of the lack of mutant structures, distances are measured from the C β of the substituted amino acid.…”
Section: Resultsmentioning
confidence: 99%
“…One study focused on the KIE of FDH WT (based on the structure of Pseudomonas sp. FDH) and on the interpretation of the KIE in the context of enzymatic reactions [263]. The other study was building on the effects observed from Val123 mutation [225].…”
Section: Low-frequency Oscillations In Formate Dehydrogenasementioning
confidence: 99%